Biodiesel production from raw cottonseed oil and its characterization - Altun, Sehmus; Yasar, Fevzi; Oner, Cengiz (Sila Science, 2011)
In this study, raw cottonseed oil of Turkish origin was transesterified using methyl alcohol and an alkali catalyst to obtain the cottonseed oil methyl ester. The obtained cottonseed oil methyl ester was analyzed by gas chromatography (GC) for determining the fatty acid composition. The fuel-related properties of cottonseed oil methyl ester, cold filter plugging point, cloud point, kinematic viscosity, density, cetane index, flash point, distillation, sulfur content and heating value were determined and compared with those of petroleum diesel fuel and international biodiesel standards. From gas chromatograph analysis, it was found that the cottonseed oil methyl ester has the more amount of total unsaturated FA, therefore, it showed better cold-flow properties than more saturated ones, as expected. Moreover, the fuel-related properties of cottonseed oil methyl ester were within the specified standards.
Keywords: Biodiesel; Cottonseed oil; Fuel Properties; GC analysis